2021
DOI: 10.1007/s00520-021-06609-8
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin supplementation for taste and smell abnormalities among patients receiving cancer chemotherapy

Abstract: Purpose: Taste and smell abnormalities (TSA) are common in patients receiving chemotherapy and may lead to altered nutritional intake, treatment withdrawal, and impaired quality of life. Lipid peroxidation in the oral cavity is one cause of TSA. Lactoferrin (LFN), an iron-binding salivary protein, reduces production of lipid oxidation byproducts and has been shown to reduce perception of unpleasant avors. To assess the feasibility of LFN as a treatment for TSA, we conducted pilot investigations among patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The salty taste is the one affected most frequently, while bitter and metallic tastes are also frequently reported as CT side effects. This may be due to different reasons, such as the presence of metallic- or bitter-tasting components in the structure of the drugs reaching the taste receptors by diffusion through capillaries (e.g., platinum contained in cisplatin and carboplatin drugs) [ 5 , 35 , 36 ], the production of carbonyls by the lipid peroxidation of oral epithelial cells causing metallic taste sensations [ 5 ], and the reduced threshold for metals described in cancer patients undergoing CT [ 35 ]. The iron-containing compounds in red meat can exacerbate these impaired sensations, explaining why many cancer patients experience a bitter or metallic taste during its consumption and prefer the use of plastic instead of metal cutlery and utensils during meals [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The salty taste is the one affected most frequently, while bitter and metallic tastes are also frequently reported as CT side effects. This may be due to different reasons, such as the presence of metallic- or bitter-tasting components in the structure of the drugs reaching the taste receptors by diffusion through capillaries (e.g., platinum contained in cisplatin and carboplatin drugs) [ 5 , 35 , 36 ], the production of carbonyls by the lipid peroxidation of oral epithelial cells causing metallic taste sensations [ 5 ], and the reduced threshold for metals described in cancer patients undergoing CT [ 35 ]. The iron-containing compounds in red meat can exacerbate these impaired sensations, explaining why many cancer patients experience a bitter or metallic taste during its consumption and prefer the use of plastic instead of metal cutlery and utensils during meals [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported an increased expression of salivary immune proteins at proteomic analysis, which are associated with taste bud growth, neutral signal transduction, and taste threshold recovery [ 78 ]. Lactoferrin supplementation (750 mg daily for 30 days) was successfully reported to improve taste scores by 1.9 points (similar score 0–10, based on nine questions on taste changes, p = 0.001) among 26 cancer patients (five patients with BC) receiving CT in a single arm pilot trial [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, this can be reversed through LF intervention 69 . In a recent human clinical study (n = 26), LF supplementation (750 mg/d) for 30 days showed effective improvement in subjective taste and smell perception of cancer patients 70 …”
Section: Management Of Csd In Covid-19/pascmentioning
confidence: 99%